(untitled) - Lussier, Robert N. (Boston, 2001)
Lussier's Human Relations in Organizations: Applications and Skill Building, 5e, takes on an application/skill building approach. This approach suits professors, who want to incorporate more activities and exercises into the classroom, and students who want to be able to do more than just understand concepts, but actually apply and develop skills that they can use in their daily and professional life. The book continues to have integration balanced by a three-pronged approach: -clear concise understanding of human relations/ organizational behavior concepts; -the application of HR/OB concepts for critical thinking in the business world; and -the development of HR/OB skills. This approach allows the student to learn the concept, apply it through various applications and situational activities, and ultimately apply it to his/her own life.
Keywords: Organizational behavior,Interpersonal relations